The Effect of Dzikir Therapy in Adolescents Against Primary Dysmennorrhea - Riski Resa Oktaria (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2025)
Primary dysmenorrhea is a problem encountered with no abnormalities in the genital apparatus. One of the non-pharmacological treatment is dzikir therapy can increase endorphin hormones are hormones that provide comfort and relieve pain. The purpose of this research to identify differences in pain scale Primary Dysmennorrhea experienced Teenegers before and after the control group and the group intervention, to determine the existence the Effect of Dzikir Therapy against Primary Dysmennorrhea. The research is a quantitative research by Quasy Experimental model Non-Equivalent Control Group Design. The sample of this researchace that consis of 25 respondents in the intervention group and 25 respondents in control group. The sampling technique by using purposive sampling. Gaved by using Wilcoxon Signed Rank Test and Mann Whitney U - Test. The result of the bivariate data analysis by using a Wilcoxon Signed Rank Test in the intervention group the values p=0.000 (p<0.05), while in the control group the value 1,000 (p>0.05). The Results of Mann Whitney test analysis of the differences decrease pain scale two groups by Mann Whitney test value-average pain reduction disminorea value difference before and after the intervention is given a value of 0,000. Inconclution There is The Effect of Dzikir Therapy Against Primary Dysmennorrhea on tennegers.